Information as a tool for management decision making: a case study of Singapore (Information Research: An International Electronic Journal)
The main objective of this study was to develop an understanding of how Singapore's managers behave as information users and determine if their behavioural patterns are similar to their counterparts in other countries (as disclosed in the literature) or if it differs, in what ways. A total of 369 questionnaires were mailed to individual members of Singapore's Institute of Management. Only twenty members responded. The main focus of the survey was the relative uses of the different types of information sources. The survey also touched briefly on the relative importance of domains, and the correlation between hierarchical and functional levels. Results indicated that the types of information considered very important for decision making included Competitor Trends followed by Regional Economic Trends. Types of information considered important included Business news followed by Political, Social, and Supplier trends, Regulatory information, Use of Information Technology, Demographic Trends and New Management methods. Sources given a very high preference rating were Personal Contact for Competitor Trends and the use of Government Publications for obtaining regulatory information. Respondents also preferred use of Government Publications for Local Economic information and the use of Newspapers for Political Trends and Business News. Internal computer printouts were used for forecasting information and company performance. Subordinate managers were referred to for information on the use of technology, Forecasting, and Company Performance. Because the Company Library provided access to newspapers (very high usage) and business news, information about Political Trends, International and Local Economic Information and Competitor Trends were associated with it. However, the Company Library was perceived as a storage facility rather than a dynamic information resource. Local libraries were also used for Regional and International Economic information. Radio and television were used to obtain regional and Local Economic Information in Singapore, but were rated low in accessibility. Very high preference was given to personal contacts as a source of information. Managers in Singapore did not exploit all types of information sources available to them, mainly due to  lack of awareness, lack of information skills and lack of accessibility to world news channels.